THE INFLUENCE OF DISCIPLINE AND WORK ETHICS ON EMPLOYEE COMMITMENTS IN THE PUBLIC WORKS AND SPATIAL PLANNING DINAS IN SERANG DISTRICT - shiva rahmawati; Mela Sandra (AMAL INSANI (Indonesian Multidiscipline of Social Journal), 2020)
The purpose of this research is to know the influence of work discipline on employee commitment, to know the influence of work ethic on employee commitment and to know the influence of discipline and work ethic together with the commitment of employees in public Works department and Serang District space Based on the research results can be formulated for the value of GIS. The discipline of the employee's commitment is 0.00 < 0.05 and the T-Calculate value 7.156 > 1.991 There is a discipline influence on the employee's commitment and for the value of GIS. The work ethic of the employee's commitment 0.134 > 0.05 and the value of T- calculate 1.516 < 1.991 smaller than T-table for the influence of discipline and work ethic on employee commitment is 0.00 > 0.05 and fcalculate value 64.359 > 3.144 large Bee table of T-tables then there is a simultaneous influence of discipline and work ethic of employee commitment and a value of double coefficient of determination (R2) R Square of 0.625. This can mean that the work ethic (X1) and work discipline (X2) variables affect 62.6% of the employee's commitment (Y) while the remaining 37.4% is influenced by other factors.